Quality of life assessment in diabetic patients: validity of the creole version of the EQ-5D-5L in Reunion Island - Safieddine, Maissa; Bruneau, Lea; Soulaimana, Ibtissame; Debussche, Xavier; Lafarge, Sophie; Falissard, Bruno; Ferdynus, Cyril; Huiart, Laetitia (Frontiers in Psychology, 2023)
Introduction: Due to the high prevalence of diabetes and its complications, evaluating the patient's quality of life is critical. EQ-5D-5L is a valid tool for assessing health-related quality of life (HRQOL) in chronic diseases, including diabetes. However, no psychometric measures have been validated in a Creole-speaking population. Therefore, this study aimed for the first time to validate and cross-culturally adapt Creole and French versions of EQ-5D-5L on Type II diabetes patients in Reunion Island. Materials and Methods: The Creole translation and cross-cultural adaptation process were based on the EUROQOL methods. Internal consistency and construct validity were determined using confirmatory factor analysis (CFA) of EQ-5D-5L for both versions. CFA model for HRQOL and global fit measures were calculated based on the EQ-5D-5L items using the maximum likelihood (ML) method. Results: From November 2016 to October 2017, 148 patients were included in the Creole group and 152 in the French group. EQ-5D-5L measures were unidimensional for both versions. Cronbach's coefficient alpha was 0.76 for the Creole version and 0.81 for the French version in CFA models. The root mean square error of approximation (RMSEA) was 0.06 for the Creole version and 0.02 for the French version. The Comparative Fit Index (CFI) was closer to 1 for both versions. CFA models for both the Creole and French versions fit the data adequately. Discussion: Overall, our findings provided evidence that both the Creole and French versions of EQ-5D-5L are suitable for assessing HRQOL in diabetes patients in Reunion Island. However, further research could be done to investigate French–Creole differences concerning the perception of health status, and a cultural adaptation of the French version will be considered.